2010
DOI: 10.1137/090764049
|View full text |Cite
|
Sign up to set email alerts
|

On the Approximation Quality of Markov State Models

Abstract: We consider a continuous-time Markov process on a large continuous or discrete state space. The process is assumed to have strong enough ergodicity properties and to exhibit a number of metastable sets. Markov state models (MSMs) are designed to represent the effective dynamics of such a process by a Markov chain that jumps between the metastable sets with the transition rates of the original process. MSMs have been used for a number of applications, including molecular dynamics, for more than a decade. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
266
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(266 citation statements)
references
References 25 publications
0
266
0
Order By: Relevance
“…Recently the interest in MSMs has increased a lot, for it had been demonstrated that MSMs can be constructed even for very high dimensional systems [25]. They have been especially useful for modelling the interesting slow dynamics of biomolecules [21,[28][29][30][31][32] and materials [33] (there under the name "kinetic Monte Carlo"). If the system exhibits metastability and the jump process between the metastable sets are approximately Markovian, the corresponding MSM simply describes the Markov process that jumps between the sets with the aggregated statistics of the original process.…”
Section: Markov State Modelsmentioning
confidence: 99%
“…Recently the interest in MSMs has increased a lot, for it had been demonstrated that MSMs can be constructed even for very high dimensional systems [25]. They have been especially useful for modelling the interesting slow dynamics of biomolecules [21,[28][29][30][31][32] and materials [33] (there under the name "kinetic Monte Carlo"). If the system exhibits metastability and the jump process between the metastable sets are approximately Markovian, the corresponding MSM simply describes the Markov process that jumps between the sets with the aggregated statistics of the original process.…”
Section: Markov State Modelsmentioning
confidence: 99%
“…24,31,32 The error incurred by the discretization and by the subsequent approximation of the jump-process as a Markov process can be systematically controlled and evaluated. 7,[33][34][35] a) B. Trendelkamp-Schroer and H. Wu contributed equally to this work. b) Electronic mail: frank.noe@fu-berlin.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter τ is called lag time and is crucial for the quality of the Markov model. 7,33 Next, one computes the transition matrix either by maximizing the likelihood, i.e., the probability over all possible Markov model transition (or rate) matrices that may have generated the observed transition counts 7,36,37 or by sampling Markov models from the posterior distribution. [38][39][40][41][42] A maximum likelihood estimate gives a single-point estimate, i.e., a single Markov model that is "most representative" given the data.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has a long tradition in chemistry, and, in particular, in the concise description of population changes in chemical reaction kinetics. Such projections onto discrete sets of states naturally lead to descriptions of the dynamics in terms of Markov state models 14 or coarse master equations 15,16 with discrete timestepping or continuous dynamics, respectively. Coarse master equations and Markov state models have attracted much attention because they can be constructed directly from molecular dynamics simulations, [15][16][17][18][19][20][21] with the aim to capture the dynamics of most interest, occurring over long time scales.…”
Section: Introductionmentioning
confidence: 99%